Soil shear resistance and plant community recovery after disturbance in a montane riparian ecosystem - Bliss, Shaan T., author; Trlica, Milton Joe, advisor; Leininger, Wayne, committee member; Cooper, David, committee member (Colorado State University. Libraries, 2011)
Vegetation recovery after a severe cattle trampling disturbance was studied in a montane riparian community. The disturbance allowed for the successful establishment of cuttings of mountain willow (Salix monticola Bebb.). However, most of the planeleaf willow (S. planifolia) cuttings had very poor establishment. Weedy annual forbs were present after the first and second years following the grazing disturbance. But, after six years of recovery the weedy forbs had declined and the dominant sedge (Carex spp.) community returned. However, some introduced forbs still persisted after six years of protection from livestock grazing. Season of trampling had significant effects on herbaceous species composition and rate of recovery. Plots trampled in the fall had greater recovery of herbaceous cover (P = 0.05) and native species (P = 0.03) as compared with late spring and early summer trampling disturbances. A severe disturbance probably increased resource availability and weedy forbs quickly took advantage of these resources. Plots trampled in the late spring retained the greatest (P = 0.0011) cover of ruderal species (23%), even after six years of recovery. However, other trampled plots returned to a composition dominated by native grasses and sedges. Mountain willow had greater survival (P = 0.01) and stem growth (P = 0.01) compared with planeleaf willow (Salix planifoliaPursh). Planeleaf willow's poor performance may have resulted from a combination of a deep water table depth, competition with adjacent plants, and poor transplantablity. Mountain willow tolerated lower water table depths and some competition from adjacent herbaceous plants. Belowground root-soil cores for several herbaceous species from the montane riparian community were studied using shear resistance measurements as an indicator for erosion protection. Three important grasses, a rush (Juncus spp.), and two sedge species were compared at two depths from 0 to 10 and 10 to 20 cm. In addition, tests for bulk density, texture, belowground biomass, and organic matter content were made to establish relationships of these variables with vegetation type and soil shear resistance. Soil cores from vegetated areas were compared with unvegetated areas. These comparisons reveled a three-fold greater (P = 0.003) shear resistance (greater protection from erosion) for vegetated sites in the upper soil depth (0 to 10 cm). There was no significant difference between vegetated and unvegetated sites for the lower soil depth (10 to 20 cm). Sedges and Juncus had greater (P < 0.0001) belowground shear resistance than grasses in the top 10 cm soil layer. Both categories of species had little effect on shear resistance below the 10 cm soil layer (P = 0.1246) where belowground biomass was much less. Sedges had three times greater (P < 0.001) shear resistance in the top 0 to 10 cm compared to the bottom 10 to 20 cm soil depth. Covariate analysis showed that belowground plant biomass was the most influential component affecting shear resistance. Soil bulk density was also an important covariate. The top 10 cm of the soil layer had the largest concentration of root and rhizome biomass and lower bulk density compared to the 10 to 20 cm depth.
Keywords: disturbance; seasonal trampling; shear resistance; soil; trampling; willow stakes